2014
DOI: 10.2807/1560-7917.es2014.19.48.20978
|View full text |Cite
|
Sign up to set email alerts
|

Human and entomological surveillance of Toscana virus in the Emilia-Romagna region, Italy, 2010 to 2012

Abstract: Toscana virus (TOSV), transmitted by phlebotomine sandflies, is recognised as one of the most important causes of viral meningitis in summer in Mediterranean countries. A surveillance plan based on both human and entomological surveys was started in 2010 in the Emilia-Romagna region, Italy. Clinical samples from patients with neurological manifestations were collected during 2010 to 2012. The surveillance protocol was improved during these years, allowing the detection of 65 human infections. Most of these inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…In this study, we observed that anti-TOSV positive BDs resided mainly in municipalities of the Bologna province, while no active TOSV circulation was observed in the Ferrara province; these findings match with estimated abundance of sand flies in these two provinces of Northeastern Italy. Between 2010 and 2013, 143 cases of neuroinvasive infection caused by TOSV were identified in the Emilia-Romagna region, Northeastern Italy; the highest number of TOSV cases was recorded in the Bologna province and the lowest number in the Ferrara province [17,18]. In line with the distribution of symptomatic TOSV cases, our serosurvey identified a high circulation of TOSV in the Bologna province, with a seroprevalence of 6.8%, while no TOSV circulation was observed in the Ferrara province.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In this study, we observed that anti-TOSV positive BDs resided mainly in municipalities of the Bologna province, while no active TOSV circulation was observed in the Ferrara province; these findings match with estimated abundance of sand flies in these two provinces of Northeastern Italy. Between 2010 and 2013, 143 cases of neuroinvasive infection caused by TOSV were identified in the Emilia-Romagna region, Northeastern Italy; the highest number of TOSV cases was recorded in the Bologna province and the lowest number in the Ferrara province [17,18]. In line with the distribution of symptomatic TOSV cases, our serosurvey identified a high circulation of TOSV in the Bologna province, with a seroprevalence of 6.8%, while no TOSV circulation was observed in the Ferrara province.…”
Section: Discussionsupporting
confidence: 73%
“…Since 1999, autochthonous human cases of TOSV meningitis have been reported in the Emilia-Romagna region (Northeastern Italy), indicating local circulation of the virus [16]. In 2010, a surveillance plan to monitor human arboviral cases was adopted by the Emilia-Romagna region, leading to the detection of 61 cases of TOSV meningitis or meningoencephalitis in 2010-2012 [17] and 82 cases in summer-autumn 2013 [18]. Two sand fly species are present in the Emilia-Romagna region, i.e., Ph.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last decade, existing and novel phleboviruses have been described. Several new phlebovirus detection and isolations have recently been reported globally , Papa et al 2011, Calzolari et al 2014, Palacios et al 2015, Baklouti et al 2016. The identified viruses could be used as a guide; year, location, and sample used for detection/isolation may give hints for possible other phleboviruses in circulation.…”
Section: Using Virology Datamentioning
confidence: 99%
“…During World War II, a large number of soldiers was affected by sandfly fever . Recently, TOSV human case records came from Italy (Serata et al 2011, Calzolari et al 2014, France (Dupouey et al 2014, Marlinge et al 2014, Portugal (Santos et al 2007, Amaro et al 2011), Croatia (Punda-Polić et al 2012, Turkey (Ocal et al 2014, Greece (Papa et al 2014), and Tunisia (Fezaa et al 2014) (Fig. 3).…”
Section: Using Medical Datamentioning
confidence: 99%